Geopolitical Risk and Stock Performance in Healthcare Industry (Case Study in Southeast Asia) - Novia Kusherawati; Taufik Faturrohman (Economics and Business Journal (ECBIS), 2026)
The healthcare industry has historically been viewed as a non-cyclical, defensive, safe haven for investors. However, the post-pandemic period has revealed the industry's susceptibility to disruptions in global supply chains and geopolitical tensions. The present research examines the effects of Geopolitical risk (GPR) on the stock performance of 76 publicly listed healthcare companies in Southeast Asia (Indonesia, Malaysia, the Philippines, Thailand, Vietnam, and Singapore) during 2015-2024. According to the Caldara and Iacoviello GPR Index, this study utilizes Panel Autoregressive Distributed Lag (ARDL) the results show that though general Geopolitical Risk and Inflation are strongly negatively impacting the stock performance, specific Geopolitical Acts (GPRA) and Threats (GPRT) are having a positive response indicating a necessity premium in which investors expect a boom in demand of medical supplies once a conflict is realized. It concludes that the healthcare industry is not a safe haven but a highly fragmented environment in which inflation poses a greater threat to companies than political instability. The study advises that investors should consider a bottom-up approach, specifically micro-resilience screening, and that corporate managers should focus on supply chain decoupling and inflation hedging to address the Resilience Gap identified in the region.